Antibacterial Activity of Disinfectants Against Staphylococcus aureus Isolated from Healthcare Equipment in Some Kano Metropolitan Hospitals (Journal of Environmental Microbiology and Toxicology, 2025)
This study investigated the antibacterial activity of common hospital disinfectants, Dettol, Hypo, and Izal, against Staphylococcus aureus isolated from healthcare equipment in selected hospitals within Kano Metropolis, Nigeria. A total of 288 samples were collected from the hospital environment, including bed sheets, bed rails, toilet door handles, and Nurses' used gloves across Imam Wali General Hospital, Muhammad Abdullahi Wase Teaching Hospital, and Murtala Muhammad Specialist Hospital. Bacterial isolation and identification were conducted using standard microbiological methods, including culture on Mannitol Salt Agar and biochemical tests. Results showed that S. aureus was the predominant isolate (30.06%), followed by E. coli (27.27%), Klebsiella pneumoniae (22.02%), and Pseudomonas aeruginosa (8.39%). The antibacterial efficacy of the disinfectants was assessed using the disc diffusion method at varying concentrations (100%, 50%, 25%, and 12.5%). Statistical analysis (ANOVA, p < 0.05) revealed significant differences among the disinfectants. Hypo (sodium hypochlorite) demonstrated the highest mean zone of inhibition across all concentrations (21.26 mm at 100%), followed by Izal (18.06 mm) and Dettol (17.58 mm), while ethanol (control) exhibited the least activity (11.83 mm). The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) results further confirmed Hypo's superior efficacy (MIC = 0.08 mL; MBC = 0.05 mL). These findings highlight Hypo as the most effective disinfectant against S. aureus isolated from hospital surfaces, likely due to its strong oxidative mechanism via hypochlorous acid production. The study underscores the importance of using highly effective disinfectants like Hypo in infection control protocols to reduce the risk of nosocomial infections and limit the spread of antimicrobial-resistant pathogens in healthcare facilities.
Keywords: Disinfectants; Staphylococcus aureus; sodium hypochlorite; Antibacterial activity; Hospital environment